A thermoelectrically stabilized aluminium acoustic trap combined with attenuated total reflection infrared spectroscopy for detection of Escherichia coli in water. Issue 9 (19th March 2021) - Freitag, Stephan; Baumgartner, Bettina; Radel, Stefan; Schwaighofer, Andreas; Varriale, Antonio; Pennacchio, Angela; D'Auria, Sabato; Lendl, Bernhard
Abstract : A thermostabilized aluminium acoustic trap combined with attenuated total reflection infrared spectroscopy used to perform ultrasound-assisted E. coli detection. Abstract : Acoustic trapping is a non-contact particle manipulation method that holds great potential for performing automated assays. We demonstrate an aluminium acoustic trap in combination with attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR) for detection of E. coli in water. The thermal conductivity of aluminium was exploited to thermo-electrically heat and hold the acoustic trap at the desired assay temperature of 37 °C. Systematic characterisation and optimisation of the acoustic trap allowed high flow rates while maintaining high acoustic trapping performance. The ATR element serves not only as a reflector for ultrasound standing wave generation but also as a sensing interface. The enzyme conversion induced by alkaline phosphatase-labelled bacteria was directly monitored in the acoustic trap using ATR-FTIR spectroscopy. Sequential injection analysis allowed automated liquid handling, including non-contact bacteria retention, washing and enzyme-substrate exchange within the acoustic trap. The presented method was able to detect E. coli concentrations as low as 1.95 × 10 6 bacteria per mL in 197 min. The demonstrated ultrasound assisted assay paves the way to fully automated bacteria detection devices based on acoustic trapping combined with ATR-FTIR spectroscopy.